Christianity, Poverty and Wealth in the 21st Century Church - Pesha, Modest (Complexities of Theologies of Wealth and Prosperity: Africa in Focus, 2022)
Poverty can be defined as the collective conditions that prevent human beings from flourishing and attaining fulfillment. Poverty also is a deprivation of capabilities, empowerment and basic freedom. The African perception of poverty differs from people in other continents. While some African social and political leaders, including Christians, assert that poverty is inevitable for the African continent, some of them strongly maintain that the ‘poor are not us’, and that poverty and the state of being poor have been caused by a few wealthy people through unjust and exploitative social, economic and political structures.
free